The theoretical aspect of transhumanism within the framework of historiosophical discourse - Окорокова, Віра Вікторівна; Окорокова, В. В.; Okorokova, Vira V. (Одеса, 2020)
The article is devoted to the consideration of theoretical aspects of transhumanism in the course of historiosophical discourse. Emphasis is placed on the digitalization of society, which feeds the main issues of transhumanism, especially in the anthropological sphere. In this sense, transhumanism is the theoretical approach that proposes a futurological digression into the future of man, so to speak, from the man of the present physical type to the posthuman. Man is understood here as an object of experimentation to apply to him innovative biotechnologies aimed at artificially improving his physical capabilities. It is about solving one of the main problems – immortalism (immortality). The article presents the opinions of scientists from two poles of transhumanism research – positive and debatable. In particular, based on the works of wellknown ideologues of this scientific trend (N. Bostrom, R. Kurzweil, J. Huxley) points to a pronounced projective feature of transhumanism, which in turn contributed to the debate among scientists about the impossibility or danger of implementing a transhumanist program of transformation. The article reveals the origins of transhumanism, and most importantly the views of scholars on this issue. There was some bipolarity in the study of transhumanism in relation to humanism and postmodernism. On the one hand, transhumanism is seen as the embodiment of some humanistic and postmodernist elements. On the other hand, there are fundamental differences, such as the understanding of the human race is not the end of our evolution, but its beginning. Hence such concepts as “transhuman” and “posthuman”, where the first type is understood as a transitional stage to the decisive stage – post-human. Anthropotechnological factor permeates transhumanism, creating a futurological program of transformation of all spheres of life, taking into account the cosmic level. The article notes that these theoretical characteristics of tran- shumanism lead some scholars (A. Shcherbina) to the idea of its propensity for utopia, and a utopia of global scale.

Стаття присвячена розгляду теоретичних аспектів трансгуманізму в напрямі історіософського дискурсу. Увага акцентується на цифровізації суспільства, що живить основні питання трансгуманізму, особливо стосовно антропологічної сфери. В цьому аспекті трансгуманізм виступає тим теоретичним підходом, який пропонує здійснити футурологічний екскурс у майбутнє людини, так би мовити, від людини нинішнього фізичного типу до постлюдини. Людина тут розумі-ється як об’єкт експерименту для застосування до неї інноваційних біотехнологій, спрямованих на штучне удосконалення її фізичних можливостей. Йдеться про вирішення однієї з головних проблем, а саме імморталізму (безсмертя). У статті наведено думки вчених двох полюсів дослідження трансгуманізму, а саме позитивні та диску- сійні. Зокрема, на основі праць відомих ідеологів цієї наукової течії (Н. Бостром, Р. Курцвейл, Дж. Хакслі) вказується на ярко виражену проєктивну рису трансгуманізму, що сприяло поширенню дискусій серед учених про неможливість або небезпеку у реалізації трансгуманістичної програми перетворень. У статті розкрито витоки трансгуманізму і, головне, погляди вчених стосовно цього питання. Виявлено певну біполярність у вивченні трансгуманізму у спів- відношенні з гуманізмом та постмодернізмом. З одного боку, трансгуманізм розглядається як втілення деяких гуманістичних та постмодерністських елементів. З іншого боку, він має принципові відмінності, наприклад розуміння людського роду не кінцем нашої еволюції, а її початком. Звідси випливають такі поняття, як «транслюдина» та «постлюдина», де перший тип розуміється перехідним етапом до вирішальної стадії – пост-люди-ни. Антропотехнологічний фактор пронизує трансгуманізм, створюючи футурологічну програму перетворень усіх сфер життя, враховуючи космічний рівень. У статті зазначено, що такі теоретичні характеристики трансгуманізму наводять деяких учених (А. Щербина) до думки про його схильність до утопії, причому утопії глобального масштабу.
Okorokova V. V. The theoretical aspect of transhumanism within the framework of historiosophical discourse / V. V. Okorokova // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2020. - Вип. 27. - С. 38-42. DOI https://doi.org/10.32837/apfs.v0i27.918
Keywords: humanism; historiosophy; postmodernism; transhumanism; гуманізм; історіософія; постмодернізм; трансгуманізм; постлюдина; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects